Comparative Metabolomics Reveals the Microenvironment of Common T-Helper Cells and Differential Immune Cells Linked to Unique Periapical Lesions - Altaie, Alaa Muayad; Venkatachalam, Thenmozhi; Samaranayake, Lakshman P.; Soliman, Sameh S. M.; Hamoudi, Rifat (Frontiers in Immunology, 2021)
Periapical abscesses, radicular cysts, and periapical granulomas are the most frequently identified pathological lesions in the alveolar bone. While little is known about the initiation and progression of these conditions, the metabolic environment and the related immunological behaviors were examined for the first time to model the development of each pathological condition. Metabolites were extracted from each lesion and profiled using gas chromatography-mass spectrometry in comparison to healthy pulp tissue. The metabolites were clustered and linked to their related immune cell fractions. Cluster I and J in the periapical abscess upregulated the expression of MMP-9, IL-8, CYP4F3, and VEGF, while cluster L and M were related to lipophagy and apoptosis in radicular cyst, and cluster P in periapical granuloma, which contains L-(+)-lactic acid and ethylene glycol was related to granuloma formation. Oleic acid, 17-octadecynoic acid, 1-nonadecene, and L-(+)-lactic acid were significantly the highest unique metabolites in healthy pulp tissue, periapical abscess, radicular cyst, and periapical granuloma, respectively. The correlated enriched metabolic pathways were identified, and the related active genes were predicted. Glutamatergic synapse, (16-20)-hydroxyeicosatetraenoic acids, lipophagy, and retinoid X receptor coupled with vitamin D receptor were the most significant enriched pathways in healthy control, abscess, cyst, and granuloma, respectively. Compared to the healthy control, significant upregulation in the gene expression of CYP4F3, VEGF, IL-8, TLR2 (P˂0.0001), and MMP-9 (P˂0.001) were found in the abscesses. While IL-12A was significantly upregulated in cysts (P˂0.01), IL-17A represents the highest significantly upregulated gene in granulomas (P˂0.0001). From the predicted active genes, CIBERSORT revealed the existence of natural killer cells, dendritic cells, pro-inflammatory M1 macrophages and anti-inflammatory M2 macrophages in different proportions. In addition, the single nucleotide polymorphism related to IL-10, IL-12A and IL-17D genes were shown to be associated with periapical lesions and other oral lesions. Collectively, the unique metabolism and related immune response shape up an environment that initiates and maintains the existence and progression of these oral lesions, suggesting an important role in the diagnosis and effective targeted therapy.